A taxonomic revision of orthotrichaceae (MUSCI) with contributions to the biosystematics of Macromitrium brid. in Malaysia / Yong Kien Thai - Yong, Kien Thai (2010)
Macromitrium (Orthotrichaceae) is a large genus variously divided into infrageneric groups by different authors, resulting in a complex classification which has not included many Malaysian species. This study reviews the taxonomy of Malaysian taxa and extent of morphological variation in relation to the type group. A molecular phylogenetic study was carried out to determine if Malaysian Macromitrium species represented a homogeneous taxonomic grouping. A cladistic analysis of morphological characteristics was attempted for identifying well-defined groups and their key character states. Molecular studies included Maximum Parsimony and Bayesian Inference analyses of two chloroplast DNA regions (rps4 gene and trnL-trnF interspecific region) for an Orthotrichaceae ingroup including representative Orthotrichoideae and Macromitrioideae, the latter comprising various genera and ten Malaysian, and two extra-Malaysian, species of Macromitrium. The outgroup included Bartramiaceae, Bryaceae, Calymperaceae, Dicranaceae, Hedwigiaceae, Pottiaceae and Rhizogoniaceae from other orders. A total of 27 species and three varieties in six genera were enumerated for the Orthotrichaceae. The majority (17 species including 3 varieties) are in Macromitrium. An identification key, species descriptions, notes and illustrations are provided. Two new species (Desmotheca mohamedii ined. and Groutiella kelantanense ined.) and two new varieties (Macromitrium longipilum var. ligulatum ined. and M. longipilum var. rugosum ined.) are proposed. All Orthotrichaceae taxa in Malaysia (including seven endemics) are tropical in origin, with nearly half restricted to Malesia. The remainder are mainly Asiatic, except a paleotropical species and three pantropical species. The molecular analyses resolved both subfamilies Orthotrichoideae and Macromitrioideae as sister clades, with Leratia basal to them in the Maximum Parsimony analysis and hence of uncertain position in the current subfamilial classification. Both large genera, Orthotrichum (Orthotrichoideae) and Macromitrium (Macromitrioideae) were paraphyletic, with several species-groups (including the type group) being resolved by the molecular analyses as different clades. The morphological cladistic analysis identified the same monophyletic type group with a divided peristome and sparsely hairy calyptra as shared group characters but it was not possible to regard these as true synapomorphies because two other putative Macromitrioideae genera (Macrocoma and Matteria) that also had these character states were not included in the analysis. In the molecular study, Zygodon (including Pleurorthotrichum) and Schlotheimia were resolved as monophyletic groups. The relationships among Desmotheca, Groutiella and Macromitrium, as well as other related genera, remain unclear, as there was generally poor resolution in the molecular phylogenetic study. Overall, it was possible to affirm the distinctness of the two subfamilies of Orthotrichaceae, the basal uncertain position of Leratia, the heterogeneous nature of both Orthotrichum and Macromitrium, and the apparent distinctness of the smaller genera Zygodon (including Pleurorthotrichum) and Schlotheimia. The positions of Sehnemobryum, Stoneobryum, Nyholmiella, Ulota, Desmotheca and Groutiella remain unclear. There was insufficient resolution in both morphological and molecular analyses to support any of the infrageneric groups proposed for Macromitrium thus far. The present study provides only a regional perspective of this speciose pantropical genus, so that a more complete understanding of the phylogeny and classification of Macromitrium would only be possible with a wider taxon sampling and the use of more informative gene regions.